Coherent quantum control of nitrogen-vacancy center spins near 1000 kelvin - Gang-Qin Liu (Nature Portfolio, 2019)
The spins of nitrogen vacancy centres have been shown to be sensitive, high-temperature quantum probes of magnetic fields but the usual readout scheme fails above 550 K. Here the authors demonstrate coherent control and sensing up to 1000 K by using fast temperature control to reach the conditions for readout.